DEVELOPMENT OF LEADERSHIP BASED ON VALUE ON FAMILY COMPANY TO SUSTAIN THE BUSINESS SUCCESS FROM GENERATION TO GENERATION - Saputra, Nopriadi (Jurnal Aplikasi Manajemen, 2017)
One of the family business challenges is how to sustain the business success from generation to generation. PT Sandimas Intimitra made a strategic decision to develop values-based leadership when the founder decided to retire and the second generation took over the leadership roles of business. This paper based on three research questions: (1) at what level is the leadership capacity of the current managers, (2) what kinds of values are relevant to be cultivated for the whole organization (3) what are the initiative programs to be developed for cultivating the values role for the whole organization?. This study used a mixed method approach, which is a combination of quantitative and qualitative approaches. A qualitative approach was used to answer the question what kind of values are relevant to be cultivated?. The qualitative approach used the 5D cycles of appreciative inquiry. While the quantitative approach used descriptive statistics to answer: at what level is the leadership capacity of the current management board and what are the initiative programs to be developed for cultivating the values role for the whole organization The conclusion of this research are: (1) PT Sandimas Intimitra need to increase the leadership capacity of the current managers, (2) there are seven values that are relevant to the new vision and mission to be cultivated, namely: integrity, responsibility, sense of belonging, learning, creative, consistent and quality, (3) the management of PT Sandimas Intimitra prosecuted for more serious role as a role model, promoter, and protector of the seven values especially creative, quality and consistent values.